Anomalous thermal conductivity of La2-xSrxCuO4: Possibility of a polaronic glass - Nuñez Regueiro, M.; Castello, D.; Izbizky, M.A.; Esparza, D.; D'Ovidio, C. (American Physical Society, 1987)
Fil: Nuñez Regueiro, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina